Poverty, deficit of effective domestic remedies and Conventionality Control - Morales Sánchez, Julieta (2025)
In a context in which the separation of powers is increasingly blurred and the democratic state is under strain, this article analyzes the need to guarantee adequate, effective, and timely legal remedies in Mexico for the comprehensive protection of human rights and for the investigation, sanction, and eradication of their violations. Drawing on the recent constitutional reform of the Mexican judiciary, which introduced the popular election of judges, the article emphasizes the importance of judicial independence from political, economic, or criminal influences, as well as the impartiality of the Judicial Disciplinary Tribunal. Within this framework, it highlights the urgency of prioritizing the exercise of conventionality control at the domestic level and the adoption of guarantees of non-repetition to comply with Mexico’s international obligations. The article also examines the obstacles faced by people living in poverty in accessing justice and refers to standards of the Inter-American Court of Human Rights to show how weakened judicial independence undermines institutional legitimacy and public trust in the democratic rule of law.